The Importance of Kinetoterapy in Multiple Sclerosis - Florentina Nechita (Editura Universitatii Transilvania din Brasov, 2023)
Multiple sclerosis is an inflammatory demyelinating disease of the central nervous system. Most of the lesions are at the level of the white matter or the junction of the white matter with the gray matter, with the periventricular region as the preferred topography. Multiple sclerosis (MS) is the leading cause of disability in young adults. The purpose of the research is based on the selection of kinetotherapeutic means and methods corresponding to multiple sclerosis, as well as the design of an individualized recovery program, so that patients who have suffered from such conditions, recover, adapt as much as possible from a somatoscopic point of view and functional. With the help of the elaborated program, the goal is to reeducate the balance and improve the ability to exercise, by restoring self-confidence, and raising the patient's morale in order to reduce certain complications of this condition.